Flow behaviour enhancement in micro-channels - Lam, Mian Mian (2017)
narrowed blood vessels, eddies are formed and thus the blood flow become turbulence. Turbulence is the main contributor to the drag as it increases the loss of energy in the form of friction. Researchers started to have great interest in investigating the feasibility of the addition of a minute amount of drag reducing additives such as soluble polymers into the flow system that resulting in a large reduction of frictional drag in blood streams. In this work, the addition of soluble polymeric additives (Xanthan gum) role as a drag reducing agent (DRA) on the drag reduction (DR) performance using microfluidic devices was investigated. Seven different geometries of Y-shaped micro-channel were fabricated and eight different soluble polymeric additive’s concentrations (20ppm to 500ppm) were used used to investigate the concentration effect on drag reduction performance using pressure measurement. The efficiency of the soluble additive was tested using transported liquid (deionised water). The experimental procedure was divided into three parts. For the first part, micro-channel devices were fabricated using soft lithography method and moulded with polydimethylsiloxane (PDMS). The second part was the preparation of soluble polymeric additives solution. Xanthan gum as the drag reduction additive was selected in this study. The last part was to run the whole experiment by using pressure and vacuum pump controller and get the flow rate measurement. The maximum flow increment (%FI) of 34.90% was achieved by utilizing 500 ppm of Xanthan gum at the operating pressure of 100mbar in micro-channel with width of 500μm. The flow behavior of the drag reducing additive into the flow was also investigated using micro particle velocimetry (μ-PIV). Furthermore, our findings proved that the natural polymers warrant further investigation as a drag reduction polymer candidate for potential clinical treatment. It was concluded that the soluble additive are believed to have strong drag reduction properties although they are used in a minute amount.